THE INCREASE IN THE NUMBER OF DENGUE CASES IN BRAZIL AND THE CORRELATION WITH DEFORESTATION AND GLOBALIZATION: A SYSTEMATIC REVIEW - Pedro do Valle Varela, João; Ronchetti Silva Cremonini, Dryelli; Edas Corteletti Pereira Lopes, Victor; Corrêa de Melo, Lucas; Correa Paes, Gabriel; Estela da Costa Azevedo, Maria; Santa Clara Prado, Matheus; Carolina Nascimento Bertollo, Ana; Eduarda Lima Silva de Almeida, Maria; Luiz Teixeira Fully, Fabio (Health and Society, 2024)
Brazil has faced a significant increase in the number of dengue cases in recent decades, which represents a challenge for public health authorities. Several factors may contribute to this increase, including deforestation and globalization, which have a direct impact on the proliferation of the Aedes aegypti mosquito, the dengue vector. The aims of this study are to investigate the relationship between increased deforestation and globalization and the increase in dengue cases in Brazil and to analyse the mechanisms by which deforestation and globalization can influence the spread of dengue. The methodology in question is a systematic review, using the narrative method, using quantitative and qualitative factors to reach the expected result. The DataSus/Tabnet, Terrabrasilis, PubMed, Scopus, Web of Science and Virtual Health Library databases were also used, using the health sciences descriptors “Dengue hospitalizations”, “Deforestation and Arboviruses”, “Deforestation and Dengue” and “Globalization and Dengue”, totalling 84 works and 8 works of literature were used in the formulation of this review and 2 references were formulated through the quantitative databases. Deforestation can increase the incidence of dengue, as it creates favorable environments for the reproduction of the transmitting mosquito, such as the accumulation of water in tires, cans and abandoned containers. In addition, deforestation can lead to the migration of populations from rural to urban areas, increasing exposure to endemic areas of the disease. Globalization can also contribute to the increase in dengue cases by facilitating the transport of infected people and the mosquito vector between different regions. Increased international trade and tourism can expand the spread of the dengue virus to new areas. The increase in the number of dengue cases in Brazil is related to deforestation and globalization, which create favourable conditions for the propagation of the mosquito vector and the spread of the dengue virus between different regions. Disease control measures must take these factors into account and include actions to monitor deforestation, vector control and public health education in order to reduce the incidence of dengue in the country.